2004
DOI: 10.1177/153537020422900602
|View full text |Cite
|
Sign up to set email alerts
|

Biological Roles of Alpha-Fetoprotein During Pregnancy and Perinatal Development

Abstract: The use of alpha-fetoprotein (AFP) as a serum marker in cancer actually predates its employment in the detection of congenital defects; however, the latter use of AFP as a fetal defect marker has propelled its clinical utilization. Although the serum-marker capacity of AFP has long been exploited, less is known of the biological activities of this oncofetal protein during fetal and perinatal development. In the present review, the biological activities of AFP are discussed in light of this glycoprotein's prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 195 publications
1
95
0
Order By: Relevance
“…6F). Afp synthesis in rodents is initiated by events prior to and during implantation (35). As shown in Fig.…”
Section: ϫ21mentioning
confidence: 99%
“…6F). Afp synthesis in rodents is initiated by events prior to and during implantation (35). As shown in Fig.…”
Section: ϫ21mentioning
confidence: 99%
“…Recently, it was reported that the stomach is one of the extraovarian tissues synthesized and secreted by E 2 , and the E 2 levels in the portal vein are over ten times higher than those in the artery in normal conditions of adult male rats (Ueyama et al 2002, 2004, Kobayashi et al 2013. It is considered that much, if not all, of E 2 in the systemic circulation is derived from the stomach in immature rats.…”
Section: Discussionmentioning
confidence: 99%
“…known as the major fetal serum protein and has a very high affinity for estrogens (Lai et al 1976, Mizejewski 2004. Although a-fetoprotein is synthesized in fetal liver and yolk sacs abundantly, it reduces exponentially postnatally and regresses by 20 days (Lai et al 1976, Nayak & Mital 1977, Greenstein 1992.…”
Section: Discussionmentioning
confidence: 99%
“…AFP i s a known onc ology m arker [16,17,18]. F or t he addressed de livery of t he AI, we have us ed AF P which ha s highly s pecific re ceptors re -expressed on the m ajority o f cancer cells [19] and is up taken by them [20].…”
Section: Discussionmentioning
confidence: 99%